Anti-consumption: an integrative review to understand the current state of scientific production - Fonseca, Letícia Rodrigues da; Carvalho de Rezende, Daniel (Periódico Eletrônico Fórum Ambiental da Alta Paulista, 2023)
This paper aims to contribute to a better understanding of the current status of scientific production about anti-consumption through an integrative literature review that identifies international and national studies published in highly relevant journals. The method applied was proposed by Botelho, Cunha & Macedo (2011). A total of 101 papers published between 2011 and 2021 were selected at the end of the analyses. The objectives were to identify the main conceptual definition used in studies on this topic, the target audience, the level of analysis and arguments for anti-consumption, the most applied research method, and the scope of this research. Furthermore, this paper attempts to highlight the main criticism of this theory raised by the scholars in this field, clarify possibilities for future research and introduce a new theoretical model that summarizes how the anti-consumption phenomenon takes place in different contexts/situations according to the findings on the studies analyzed by this integrative review. Hopefully, this paper can contribute to advancing and developing this field at the theoretical and practical levels by setting a research agenda.